PRODUKSI GLUKOSA DARI JERAMI PADI (Oryza sativa) MENGGUNAKAN JAMUR Trichoderma sp. - Yuli Rismawati; Syaiful Bahri; Prismawiryanti Prismawiryanti (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
Research glucose production from rice straw (Oryza sativa) using Trichoderma sp. has conducted. This study aime is to determine the effect konsentrasi Trichoderma sp. And a straw fermentation of rice (Oryza sativa) against production. Research glucose levels was done using a completely randomized design (CRD) with factorial pattern 4 variation of the concentration of Trichoderma sp. (0%, 24%, 36% and 48%) and fermentation time (3, 4, 5and6 weeks), glucose levels were analyzed using DNS with UV-Visible spectrophotometry. The measurement results showed that the highest glucose levels obtained at various concentration Trichoderma sp. 36% fermentation time during the five week sthat is equal to 14.525%. There is a positive interaction between the concentration of Trichoderma sp. and the fermentation time, the best combination of time and fungal concentration of 5 weeks and 36%, respectively.Keywords : Rice straw, Trichoderma sp., Fermentation, DNS, Spectrophotometer Uv-Visibel, Glucose.